Territórios no espaço público: um estudo de caso nas praias de Vitória e Vila Velha-ES - Monteiro, Rafael Santos da Luz (2016)
This study aims to analyze the bond between the production of the metropolitan space of RMGV and socioterritorial content expressed on the beaches of the municipalities of Vila Velha and Vitória-ES. The analytical effort concerns the study of two scales: the beach and the city, such scales allow evaluations about the everyday and the unequal access of parts of the population to some specific parts of the beach. The frequentation or ocupation of the beach does not happen accidentally, thus, we believe that territorial strategy, constantly mediated by the distinction and social judgment, becomes a common practice in this environment, which essentially contributes to form different types of territorialities across the beach.